Investigating Novel Symmetries in Chemical and Biological Systems: Insights from Comparative Structural Analysis of Dochi Compounds - Vasilescu, Alexandru Mihai Popescu and Elena (Journal of Computer Engineering, 2022)
A unique feature of numerous plants secondary metabolites is the achievement of a stage when their molecule possesses a double set of chiral centers and of chemical functions. Of this reason, we have called them dochi (do from double, chi from chiral). Three major isomeric types or subgroups can be met inside the group of dochi: (A) meso compounds, whose molecule is characterized by a mirror plane of symmetry; (B) The second subgroup of isomers includes chiral compounds whose molecule is formed of two identical halves, and called of this reason chitwin (chi from chiral, plus twin). This subgroup had been called also C2 symmetrical compounds; in fact, they are C2 symmetrical since they are chitwin. The latter compounds are characterized by a plane (or relationship) of chitwinism, considered as a new type of virtual mirror (or relationship) showing not the image of the object, as we are used to, but an identical copy of the object. (C) The third subgroup is formed of compounds with asymmetric form, possessing only an identity operation. This subgroup includes chiral compoundsbased on an irregular disproportional distribution of the asymmetric carbons in their molecule, and called of this reason irrechi (irre from irregular, chi from chiral). Here are included only compounds which are chiral and isomers with meso and chitwin ones. All three subgroups – chitwin,meso, irrechi – are characterized by structural and metabolic relationships with other compounds. At the same time, the group of dochi includes numerous synthetic compounds, especially of chitwin type